1984
DOI: 10.1002/jcp.1041200108
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP‐dependent and ‐independent protein kinases and protein phosphorylation in human promyelocytic leukemia (HL60) cells induced to differentiate by retinoic acid

Abstract: The human leukemia cell line HL60 which resembles promyelocytes can be induced to differentiate to cells displaying features of the mature myeloid phenotype by a variety of agents including retinoic acid (RA) and agents that elevate intracellular adenosine 3:5 cyclic monophosphate (cyclic AMP) levels, e.g., 8-bromo-cyclic adenosine 3:5 monophosphate (8-Br-cyclic AMP), cholera toxin. Since most, if not all the effects of cyclic AMP, are mediated by adenosine 3:5 cyclic monophosphate-dependent protein kinase (cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…When the cell lines were cultured with TPA or RA, the 68-kD subunit was slightly induced. TPA and RA have been described to induce cell differentia tion of various cell types including murine and human neuroblastoma cells [11][12][13][14][15] and a wild type of leukemia cell line [16][17][18]. The observation that TPA may induce a major reorganization of cytoskeletal components [19,20] could explain the more significant induction of the 68 kD obtained with TPA than with RA, in 2 of the 3 cell lines tested.…”
Section: Discussionmentioning
confidence: 84%
“…When the cell lines were cultured with TPA or RA, the 68-kD subunit was slightly induced. TPA and RA have been described to induce cell differentia tion of various cell types including murine and human neuroblastoma cells [11][12][13][14][15] and a wild type of leukemia cell line [16][17][18]. The observation that TPA may induce a major reorganization of cytoskeletal components [19,20] could explain the more significant induction of the 68 kD obtained with TPA than with RA, in 2 of the 3 cell lines tested.…”
Section: Discussionmentioning
confidence: 84%
“…Thus, PKC and PKA regulate a variety of developmental and mature neuronal and nonneuronal processes. Additional studies demonstrated differentiation-specific alterations in PKC and PKA activities (Abraham et al, 1991;Durham et al, 1985;Fontana et al, 1984;Kraft and Anderson, 1993;Plet et al, 1985Plet et al, , 1986Plet et al, , 1987Wooten et al, 1992). These data suggest that alterations in PKC and PKA activities are associated with the development of the mature cellular phenotype.…”
Section: Introductionmentioning
confidence: 82%
“…RA stimulated translocation of the type II protein kinase from the cytosol to the plasma membrane in the F9 cells and to the nucleus in the erythroleukemia cells. Fon-tona et al [36] reported changes in protein phosphorylation patterns and an increase in the type I protein kinase of HL60 cells 24 h after treatment with 1 pM RA. No reproduc ible changes were found in intracellular cAMP content in HL60 cells in response to RA or DMSO [37], Cyclic AMP or its analogues alone did not markedly increase TGase activity in HL60 cells.…”
Section: Discussionmentioning
confidence: 99%